New record of Clypeasterophilus stebbingi (Rathbun, 1918) (Decapoda: Brachyura: Pinnotheridae) from the east coast of Nicaragua - Hendrickx,Michel E. (2013)
The pinnotherid crab Clypeasterophilus stebbingi (Rathbun, 1918), previously known from Florida, USA, Colombia and Brazil, is reported for the first time from Central America, on the east coast of Nicaragua. A single female specimen was collected on the sand dollar Clypeaster subdepressus (Gray, 1825), at 4 m depth, among turtle grass on sandy bottom. The specimen fits well with the description provided by M.J. Rathbun and observations made on photographs of the male holotype. Comparison of the material described from Florida (including the type material), Colombia and Brazil to the Nicaragua specimen, however, indicates that C. stebbingi shows some variation in the shape of the third maxilliped.